Tópicos de teoria dos números aplicados ao ensino básico e técnico profissionalizante - Dujardin Júnior, Iberê Nazareth (2018)
The present work is devoted to the provision in theoretical knowledge in topics of Numbers Theory, Fibonacci Sequence and Golden Number, serving the purposes of a basis for consultation and research for teachers in basic education, high school and technical courses, improving attractive and interactive teaching of mathematics. The stages of high school and technical education were taken into account, properly justified and explained. Classroon plans for assembled and appended to this text. The proposals have been implemented and the results are compiled and discussed. At the request of enrollment it was especially directed towards High School, with emphasis on mathematical practices, not just as science, but also Architecture, among others. The present work is, therefore, a study dedicated to Mathematics Education, addressing concepts inherent in Significant Learning.